Performance augmentation of retrofitted sustainable R1234yf in R134a air conditioning system using AI2O3 SiO2 hybrid nanolubricant - M. Z., Sharif; Wan Azmi, Wan Hamzah; Mohd Fairusham, Ghazali; Hafiz, Muhammad Ali (Springer Science and Business Media B.V., 2023)
Low global warming potential hydrofluoroolefin-1234yf (R1234yf) is an alternative green refrigerant for the automotive air conditioning (AAC) system to replace the existing R134a refrigerant. However, the low energy efficiency of the AAC system using R1234yf has been a significant obstacle to its wider use. This paper describes using Al2O3–SiO2/DEC PAG nanolubricant to enhance the performance of the AAC-R1234yf system. The hybrid nanolubricant was created by a two-step preparation process. The experiment was undertaken at volume concentrations up to 0.05% and under various operating conditions. The stability test shows that the hybrid nanolubricant remained in superior stability after 6 months, with minimum particle aggregation and sedimentation. The AAC-Al2O3–SiO2/DEC PAG system achieved the best performance at 0.03% volume concentration with an average increment of 12.01%. This outcome was contributed by the increase of the AAC evaporator’s heat absorb value by 2.8% and the reduction of the compressor work with an average decrease of 7.7%. In conclusion, a 0.03% volume concentration of Al2O3–SiO2/DEC PAG nanolubricant in the AAC compressor was recommended for optimum system performance and energy saving.